Nutritional composition and antiobesity effects of germinated brown rice in vitro and in vivo - Lim, See Meng (2016)
Obesity is a condition of abnormal or excessive fat accumulation in the body that poses potential health-threatening on one person. This study was carried out to determine the nutritional values of germinated brown rice (GBR) and to investigate its potential application for obesity treatment by using in vitro and in vivo models. Nutritional composition of GBR was determined. In the in vitro study, GBR was extracted separately by employing different solvents with ultrasound-assisted method. Pancreatic lipase activity was determined spectrophotometrically. Adipogenesis and lipolysis were assayed in fully differentiated 3T3-L1 adipocytes by using Oil Red O staining and glycerol release measurement. In the in vivo study,46 male Sprague-Dawley rats were fed with either normal diet or high fat diet (HFD; 52% fat, 35% carbohydrate and 13% protein from total energy, kcal) for 8 weeks obesity induction. After obtaining their baseline data, the rats were divided into five groups: normal diet control (NC), HFD positive control (PC), HFD supplemented with 25% GBR (25T), HFD supplemented with 50% GBR (50T) and HFD supplemented with 100% GBR (100T). Each group of the rats was provided with their respectively diets over another 8 weeks. Therapeutic effects of GBR against obesity in obese rats were studied via assessing the body weight (BW) gain, food intake level, plasma lipids profile, fasting blood glucose level and plasma leptin level. Histology of liver and adipose tissue were also performed. Energy content of GBR was 390.95 ± 11.31 kcal/100 g and carbohydrate (54.30 ± 1.04 g/100 g) was the most abundant nutrient. The predominant minerals in GBR were potassium, magnesium and sodium. In the in vitro study, GBR hexane extract showed the highest inhibitory effect (13.58 ± 0.86%) at concentration of 200 μg/ml on pancreatic lipase activity. At concentration of 300 μg/ml, water extract of GBR significantly decreased (p< 0.05) lipid accumulation compared with control with 61.55 ± 3.82% of Oil Red O staining material (OROSM), a marker of adipogenesis, followed by ethyl acetate extract (OROSM= 65.17 ± 3.13%). All the GBR extracts induced lipolysis with 1.22-1.83 fold of greater glycerol release than control. The in vivo study showed BW gain (16.88 ± 10.12 g) and food intake (12.00 ± 0.86 g) were significantly lowered (p< 0.05) in 100T group compared with other groups. The antiobesity effects of GBR in 100T group were further confirmed with the lowest in total white adipose tissue weight (4.55 ± 1.31 g/100g BW) and liver weight (2.70 ± 0.25 g/100g BW) compared with other groups. Lower plasma leptin level and improvement of plasma total cholesterol level and triglycerides level plus restoring the decrement in HDL-cholesterol level were observed in GBR administered obese rats. Higher fat excretion in the faeces, shrinking in adipocytes size and lesser micro- and macrovesicular steatosis were evident in GBR administered obese rats. In conclusion, this study showed that GBR exhibited antiobesity effects through inhibitory effect on pancreatic lipase, decrease fat accumulation by adipocyte differentiation inhibition, stimulate lipolysis on adipocytes and reduced weight gain, food intake, white adipose tissue mass and leptin level together with improvement in plasma lipid profiles and micro-and macrovesicular steatosis in HFD-induced obese rats.